Women in Harperland: A Critical Look at Gender Inequality in Canada Since 2006 - Strumm, Brianna (Canadian Review of Social Policy / Revue canadienne de politique sociale, 2015)
This paper critically examines and summarizes the facts on gender inequality under Stephen Harper’s Conservative government. Since Stephen Harper’s election in 2006, arguably, women’s economic and social well being has weakened, therefore increasing gender inequality inCanada. This paper briefly discusses current national trends with regards to pay inequity, precarious employment options, income splitting, social infrastructure such as childcare and the Universal Child Care Benefit (UCCB) and lastly, violence against women. This paper additionally argues that with the near disappearance of the Status of Women Canada’s mandate, women are being written out of the national story; currently, the budget for Status of Women Canada amounts to a mere 0.03% of direct federal program spending (McInturff, 2014). TheRoyal Commission on the Status of Women took place nearly 45 years ago and another wide-sweeping, national look at women’s lives in Canada is again required to ensure equality and the full participation of women in the 21st century. Proper attention to women’s issues and genderequality is a matter of fairness. Non-discrimination is a Charter-guaranteed right for women in Canada.Cet artticle examine et résume de façon critique les réalités sur l’inégalité entre les genres sous le gouvernement conservateur de Stephen Harper. Le bien-être économique et social des femmes s’est affaibli depuis l’entrée au pouvoir de Stephen Harper en 2006, ce qui a eu comme résultat d’augmenter l’inégalité entre les genres au Canada. Cet article discutebrièvement des tendances nationales en ce qui a trait à la disparité salariale, aux conditions précaires d’emploi, à la séparation des revenus, et aux infrastructures sociales telles la garde des enfants, et la prestation universelle pour la garde des enfants (PUGE), et finalement, laviolence envers les femmes. De plus, cet article propose qu’avec la quasi-disparition du mandat de la condition féminine Canada, les femmes sont en train d’être supprimées de l’histoire nationale. Présentement, le budget annuel de la condition féminine Canada est à peine 0.03% des dépenses directes fédérales de programmes sociaux (McInturff, 2014). La commission royale sur le statut des femmes a pris place il y a plus de 45 ans, et il semblerait qu’un autre regard national et général sur la vie des femmes canadiennes est de nouveau de mise afin de garantir la participation totale des femmes au 21ième siècle. Les problématiques des femmes et de l’égalité entre les genres sont des questions d’équité, et la non-discrimination est un droit garanti par la charte des droits humains au Canada.Mots-Clefs: Inégalités entre les genres; violence envers les femmes; disparité salariale;garde des enfants